Stabilization of organic matter in the raised-bed soils of tidal swamplands is influenced by the types and the amounts of organic matter application - A R Saidy; I Khairullah; M Septiana; E Triatmoko (Center for Journal Management and Publication, 2014)
Farmers in tidal swamplands annually added organic matter (OM) onto the raised beds to maintain organic matter contents and thereby maintain soil productivity of the raised beds. This experiment aimed to study the influence of the types and the amounts of OM on the stabilization of organic matter in the raised-bed soils. Four types of OM: rice straw, eceng gondok (Eichornia crassipes), purun tikus (Eleocharis dulcis) and mixed rice straw-eceng gondok were added to a 27-year raised bed soil with 4 different rates: 0, 0.5, 1.0 and 2.0 of maximum sorption capacity (Qmax), and the OM stabilization was quantified after 10 weeks of OM addition. Results of this study showed with the exception of rice straw, OM addition to soil resulted in increases in the mineralization of soil OM thereby inducing priming effect. Addition of rice straw at rate of 0.5 of Qmax resulted in stabilization of 46% added OM, while only 30% and 37% of added OM was stabilized when OM was added to soils at rates of 1.0 and 2.0 Qmax, respectively. This study showed that the stabilization of OM in raised bed soils were influenced by the chemical composition of OM and the amount of added OM.